2021
DOI: 10.1039/d1ra06842c
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS analysis of phytoconstituents from Ruellia prostrata and Senna tora and identification of potential anti-viral activity against SARS-CoV-2

Abstract: Protease (Mpro) of SARS-CoV-2 has been identified as being able to hinder the replication process of the virus. Using GC-MS analytical methods, phytochemicals were identified from different medicinal plants that resulted in inhibitory activity of the molecules against Mpro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…Other existing drugs, such as lopinavir, oseltamivir, ritonavir, atazanavir, darunavir, plitidepsin, testosterone, progesterone, hydroxychloroquine, tetracyclines, flaviolin, hydroxyethylamine analogs, buriti oil (mauritia flexuosa L.) like inhibitors, etc., were also investigated specifically by docking and MD simulations. 397 , 614 , 1048 1073 …”
Section: Methods and Approachesmentioning
confidence: 99%
“…Other existing drugs, such as lopinavir, oseltamivir, ritonavir, atazanavir, darunavir, plitidepsin, testosterone, progesterone, hydroxychloroquine, tetracyclines, flaviolin, hydroxyethylamine analogs, buriti oil (mauritia flexuosa L.) like inhibitors, etc., were also investigated specifically by docking and MD simulations. 397 , 614 , 1048 1073 …”
Section: Methods and Approachesmentioning
confidence: 99%
“…Compound pharmacokinetics and compound pharmacodynamics are used in such models. COVID-19, an infectious viral disease, is the most recent example of how mathematical models are employed in drug discovery [36].…”
Section: Mathematical Models In Drug Designmentioning
confidence: 99%
“…A prior study has used GC-MS analysis to identify fifty-six bioactive compounds from a methanolic extract of Tinospora crispa, in which the top nine hits showed a strong affinity with the SARS-CoV-2 main protease (Mpro) enzyme [22]. Similarly, a recent study has found that Ruellia prostrata and Senna tora extracts contained a total of forty-three and fifty-three phytochemicals, respectively, identified through the GC-MS analytical method, in which the best four compounds were selected for future drug development based on molecular docking and MD simulation analyses [23]. The plant metabolites including terpenoids, polyphenols, and phytosterols of natural origin have potential pharmacological and medicinal applications in various stages of basic and clinical research.…”
Section: Gc-ms Analysis Of Moringa Oleifera Leafmentioning
confidence: 99%